Cooking characteristic and sensory evaluation of cauliflower leaves incorporated homemade noodles (Journal of Food and Dietetics Research, 2021)
Objectives: The present study was carried out with the objective of examining the cooking and sensory attributes  of cauliflower leaves (Brassica oleraceavar. botrytis) incorporated homemade noodles.  Material and Methods: Noodles in ratio 60:40 (WF:PMF) served as control and the cauliflower leaves puree (CLP)  was incorporated to the control noodles in five different proportion such as 10, 20, 30, 40, and 50. The various  blends were processed and shadow dried to prepare noodles. Both dry and cooked noodles were subjected to  sensory evaluation by trained panel members and the cooking characteristics were estimated.  Results: The water absorption of the noodles increases with increase in the level of CLP, cooking loss reduced with  the level of CLP incorporation and was statistically significant at P
Keywords: Noodles; Pearl millet; Antioxidant; Cauliflower leaves; Homemade